Perkembangan Literasi Digital Bahasa Arab : Peluang dan Tantangan Era 5.0 - Avika Afdiana Khumaedi (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
This study aims to analyze the role and challenges of the Arabic language in the digital context, particularly in the 5.0 technology era. Using a qualitative approach based on literature review, this research examines technological advancements in Arabic language learning through the analysis of various documents, including journals, books, and related publications. The findings indicate that digital technology has opened up significant opportunities in Arabic language learning, such as online teaching, the digitization of classical literature, and personalized learning using artificial intelligence. However, there are notable challenges, such as the digital divide, limited technological skills among educators, and the complexity of digitizing classical manuscripts. The implications of this study highlight that digital literacy is a crucial element in Arabic language teaching in the modern era. This research also emphasizes the need for digital training for educators and the development of more inclusive technologies to support broader access to Arabic language learning.